2023
DOI: 10.12688/f1000research.130285.1
|View full text |Cite
|
Sign up to set email alerts
|

A review of recent advances in the diagnosis of cardiac amyloidosis, treatment of its cardiac complications, and disease-modifying therapies

Abstract: Cardiac amyloidosis (CA), a significant condition resulting in infiltrative cardiomyopathy and heart failure with preserved ejection fraction (HFpEF), is caused by extracellular deposition of amyloid fibrils in the heart. Even though this has been known for an extended period, its prevalence in elderly patients with heart failure is increasingly being recognized. Recent advances in diagnosis with non-invasive methods like technetium pyrophosphate-labeled cardiac scintigraphy (i.e., Tc-PYP scan) and treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Since AL and ATTR are responsible for 95% of CA cases, the diagnostic work-up focuses on differentiating between these subtypes of CA. All patients with suspected CA should undergo assessment for the presence of monoclonal protein in serum and urine, by serum protein electrophoresis with immunofixation (SPIE), urine protein electrophoresis with immunofixation (UPIE) and serum kappa/lambda free light chains ratio [ 13 , 23 , 24 ]. Serum kappa/lambda light chains ratio is considered normal between 0.26–1.65, by Freelite assay, and 0.53–1.51 by N latex assay.…”
Section: Diagnostic Algorithmmentioning
confidence: 99%
“…Since AL and ATTR are responsible for 95% of CA cases, the diagnostic work-up focuses on differentiating between these subtypes of CA. All patients with suspected CA should undergo assessment for the presence of monoclonal protein in serum and urine, by serum protein electrophoresis with immunofixation (SPIE), urine protein electrophoresis with immunofixation (UPIE) and serum kappa/lambda free light chains ratio [ 13 , 23 , 24 ]. Serum kappa/lambda light chains ratio is considered normal between 0.26–1.65, by Freelite assay, and 0.53–1.51 by N latex assay.…”
Section: Diagnostic Algorithmmentioning
confidence: 99%
“…Recent studies have implied that the prevalence of ATTR cardiac amyloidosis might not reflect the actual number in the population, as it is often underdiagnosed. 1,3,5,6 ATTR is further classified into two major phenotypes: ATTRv, which is characterized by inherent mutation of the transthyretin gene, and ATTRwt, which is mainly associated with age-related alterations. 3,5,7 ATTRv is highly prevalent among the black male population, while most subtypes of amyloidosis affect both sexes equally.…”
Section: Introductionmentioning
confidence: 99%
“…Protein misfolding and aggregation occur due to factors such as abnormal proteolysis, point mutations, and posttranslational modifications like phosphorylation, oxidation, and glycation. 3,4 Research conducted in Germany examined trends in hospitalizations for heart failure and found that improved outcomes were partially attributed to the utilization of percutaneous coronary interventions. 5 Another investigation focused on patients diagnosed with cardiac amyloidosis and revealed that individuals with ST-elevation myocardial infarction and cardiac amyloidosis had higher rates of signs and symptoms, including ventricular tachycardia/ventricular fibrillation, cardiogenic shock, acute kidney injury requiring dialysis, and admissions to the intensive care unit, compared to those without ST-elevation myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%